Collagen Hydrolysate Supplementation and Cellular Landscape Remodeling in Gunshot Wounds - Bezpalko, M. (Journal of Education, Health and Sport, 2025)
Background. Gunshot wounds (GSWs) are severe ballistic injuries characterized by massive tissue destruction, ischemia, and oxidative stress, resulting in impaired wound repair. The study aimed to evaluate the effect of oral collagen hydrolysate supplementation on cellular dynamics, angiogenesis, and collagen matrix remodeling in gunshot trauma under experimental and clinical conditions. Material and Methods. The research was conducted at Odesa National Medical University (2022–2025) and included experimental and clinical phases. Forty male rats with standardized gunshot-type wounds were divided into two groups: control and collagen-supplemented (500 mg/kg for 14 days). Histological, morphometric, and immunohistochemical analyses (CD163+ macrophages) were performed to assess fibroblast proliferation, angiogenesis, and collagen maturation. The clinical study involved 80 male patients (20–59 years) with extremity GSWs: 42 controls (standard treatment) and 38 receiving oral collagen hydrolysate (10 g/day for 45–60 days). Clinical, biochemical, and morphological indicators of healing were recorded. Statistical significance was set at p<0.05. Results. In the experimental model, collagen hydrolysate reduced wound necrosis by 36%, increased fibroblast density by 77%, and elevated hydroxyproline content from 0.62±0.07 to 1.38±0.09 mg/g (p<0.001). M2 macrophages increased to 57±6% (vs 31±5% in controls), while collagen type I/III ratio rose to 0.93±0.06. In patients, epithelialization accelerated by 5 days (19.6±1.8 vs 24.8±2.1; p<0.001), complications decreased by 54%, and hospital stay shortened by 6 days. Hydroxyproline rose by 50%, and pathological scarring incidence halved. Conclusions. Collagen hydrolysate significantly accelerates wound healing by enhancing fibroblast activity, angiogenesis, and collagen organization. It is a safe, cost-effective adjunct to surgical management, suitable for both civilian and military trauma, with potential to reduce hospitalization, improve scar quality, and enhance functional recovery. (≈250 words)